Lest We Forget the Realm of Armed Conflicts: A Guided Discussion on the Law of Armed Conflict/International Humanitarian Law - Sangroula, Yugichha (Kathmandu School of Law Review, 2019)
The paper is a doctrinal and a dialectic endeavour to comment on LOAC/IHL from a bird’s-eye view. It is the author’s initial attempt to contribute to an ongoing discussion on the theory and practice of LOAC/IHL, reflecting on the key issues relevant to Nepal. The question-answer approach is based on the author’s interactions with law students, colleagues, members from the police, military, victims, bureaucrats and politicians in the Nepali diaspora. The paper will benefit from the readers’ critique.